A survey to document toxic hazards in the zone surrounding volcanoes national park, a habitat for mountain gorillas, an endangered wildlife species in Rwanda - Kwizera, Enock; Rumbeiha, Wilson K.; Nishimwe, Kizito; Nziza, Julius (Frontiers in Veterinary Science, 2024)
In recent years, Volcanoes National Park has seen a rise in its wildlife population, primarily due to the diligent efforts of the Rwandan government in safeguarding endangered species, notably the mountain gorillas (Gorilla beringei spp. beringei). This population growth has led to a pressing need for more expansive habitats, ensuring these creatures have ample space, sustenance, and shelter for their wellbeing. Consequently, there are planned park expansion activities on the horizon. However, before initiating this expansion, a critical prelude involves identifying potential threats, particularly toxic substances stemming from agricultural activities in the surrounding environment of Volcanoes National Park. To address this concern, by using a survey sampling, a a comprehensive study was conducted, aimed at pinpointing potential toxic hazards and assessing the awareness of the local population regarding the harm these hazards pose to wildlife species. Data was collected from individuals with no prior knowledge of the study using a pre-tested questionnaire. The questionnaire was divided into three sections: socio-demographic issues, potential toxic hazards assessment, and a section to determine awareness and risk of potential toxic hazards to humans, animals, and the environment. Respondents were selected based on specific criteria, which included being 18 years or older and residing within the National Volcano Park (NVP) area. The study's findings revealed four main categories of potential toxic hazards, which include household chemicals, pharmaceutical products, agricultural pesticides, and poisonous plants. These hazards could jeopardize the health and survival of wildlife species if they consume or come into contact with them. Furthermore, the study exposed an inadequacy in the knowledge and skills of the local community in preventing these toxic hazards, which can result in death of wildlife species and ecosystem contamination and degradation. Study results also underscored the significance of education and training in enhancing the awareness of local communities concerning these toxic threats. Therefore, it is imperative to implement immediate measures to mitigate the adverse effects of these toxic hazards on wildlife species, especially in light of the planned park expansion.